История возникновения операционного исчисления и вклад учёных в его развитие - Дубинина, Оксана Николаевна; Решетникова, Светлана Николаевна (НТУ "ХПИ", 2011)
В статье рассмотрена история возникновения операционного исчисления и вклад ученых (М. Е. Ващенко-Захарченко, А. В. Летникова, О. Хевисайда и др.), а также выпускников НТУ "ХПИ" (Я. Е. Айзенберг и др.) в его развитие.

In article the history of occurrence of operational calculation and the contribution of scientists (by M. E. Vashchenko-Zaharchenko, A. V. Letnikov, О. Heaviside, etc.), and also graduates of National technical university „Kharkov polytechnical institute” (J. E. Ajzenberg, etc.) in its evelopment is considered.
Keywords: выпускники; высшая математика; профессионализм; законы Сервуа; operational calculation; scientists; history of occurrence; development